Association of periodontal status with occlusal force and food acceptability in 70‐year‐old adults: from SONIC Study. (24th July 2014) - Okada, T.; Ikebe, K.; Inomata, C.; Takeshita, H.; Uota, M.; Mihara, Y.; Matsuda, K.; Kitamura, M.; Murakami, S.; Gondo, Y.; Kamide, K.; Masui, Y.; et al.
Summary This cross‐sectional study aimed to investigate the association of periodontal status with occlusal force and food acceptability. We hypothesised that mastication deteriorated with reduced periodontal support, even when posterior occlusal contacts with natural teeth were maintained and the patients remained clinically asymptomatic. Participants were 482 independently living 69‐71‐year‐olds, classified as Eichner's group A, having no mobile teeth and no periodontal symptoms. The periodontal probing depth (PPD) and restoration status of each tooth were examined. Occlusal force in the intercuspal position was measured with pressure‐sensitive films. Food acceptability was evaluated from the difficulty experienced in chewing apples, grilled beef, and hard rice crackers. Multivariate regression analysis was performed to investigate the association of periodontal status with occlusal force and food acceptability. A P‐value of <0·05 was considered statistically significant. Multiple linear regression analysis showed that occlusal force had significant negative associations with maximal PPD (standardised partial regression coefficient (β) = −0·121) after controlling for gender, handgrip strength, number of teeth, and percentage of restored teeth. Approximately 15% of participants were included in the compromised food acceptability group. Logistic regression analyses showed that compromised food acceptability was significantly associated with PPD, after controlling for gender, number of teeth, and percentage of restored teeth. Periodontal probing depth (PPD) was significantly correlated with occlusal force and self‐rated food acceptability after controlling for the possible confounding factors in septuagenarians, even those with complete posterior occlusal contacts and no tooth mobility.